PENGARUH PERHATIAN, KETERTARIKAN, KEINGINAN DAN KEYAKINAN TERHADAP MINAT BELI KONSUMEN PADA PT. MAHKOTA PETRIEDO INDOPERKASA - Putri Sakinah BR Hombing; Suwarno Suwarno; Cahyo Pramono (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to determine whether attention, interest, desire and belief simultaneously have a positive and significant effect on consumer buying interest at PT. Crown Petriedo Indoperkasa. The data analysis technique used is the quantitative associative method with the help of the SPSS program. This study uses multiple linear regression. The research sample was 91 respondents. Primary data collection using a questionnaire. The results showed that partial attention had a positive and significant effect on consumer buying interest at PT. Crown Petriedo Indoperkasa. Partial interest has a positive and significant effect on consumer buying interest at PT. Crown Petriedo Indoperkasa. Desire partially positive and significant effect on consumer buying interest at PT. Crown Petriedo Indoperkasa. Confidence partially positive and significant effect on consumer buying interest at PT. Crown Petriedo Indoperkasa. Attention, interest, desire and belief simultaneously have a positive and significant effect on consumer buying interest at PT. Crown Petriedo Indoperkasa.Keywords: Attention, Interest, Desire, Confidence And Buying Interest.